The Effectiveness of Distance Learning in the Education System in Uzbekistan (Journal of Pedagogical Inventions and Practices, 2024)
In today's world of information technology, distance learning is becoming increasingly important. Because this type of education differs from the existing types of education in some of its positive aspects, the difference between distance learning and full-time and other types of education is that this type of education is very popular with the general population. In this article, there is elucidated the effectiveness of distance learning in the education system of Uzbekistan